1999
DOI: 10.1177/002190969903400204
|View full text |Cite
|
Sign up to set email alerts
|

African Immigrants in the United States: A Socio-Demographic Profile in Comparison to Native Blacks

Abstract: Using data from the 1980 and 1990 U.S. censuses (5% Public Use Microdata Samples), this paper provides the socio-demographic profile of African immigrants in comparison to native blacks. The results show that the number of Africans living in the United States has increased by 6% per year between 1980 and 1990, but the growth has been greater for blacks (11%) than for whites (4%). This racial differences in growth changed the composition of the African immigrant population from predominantly white (60%) in 1980… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 10 publications
5
15
0
Order By: Relevance
“…This aligns with the findings presented by Djamba (1999) where he reported that the majority of immigrants who resettled in the US in late 1990s were more likely to be married and more educated compared to native-born Blacks. In the same vein, McCabe (2011) found not only that African immigrants were more likely to be educated, but also more likely to work in the civilian labor force compared to African-Americans.…”
Section: Discussionsupporting
confidence: 89%
“…This aligns with the findings presented by Djamba (1999) where he reported that the majority of immigrants who resettled in the US in late 1990s were more likely to be married and more educated compared to native-born Blacks. In the same vein, McCabe (2011) found not only that African immigrants were more likely to be educated, but also more likely to work in the civilian labor force compared to African-Americans.…”
Section: Discussionsupporting
confidence: 89%
“…However, there has been insufficient research conducted to explain why these disparities exist [46,47]. Historically, African immigrants and African-Americans have been studied as one racial group in the US, although health outcomes may differ in African-descent populations due to differences in socioeconomic status [48] and genetic admixture [13]. The practice of grouping of all African-descent populations into the ''Black/AfricanAmerican'' category without consideration of country of origin, masks socioeconomic and cultural differences and needs re-evaluation [49].…”
Section: Discussionmentioning
confidence: 99%
“…Most voluntary Black migrants during the early 1900s came from the Caribbean (Reimers 2005), but after US migration policy liberalized in the mid1960s migration from Africa increased, and it more than tripled between 1980 and 2005 (Kent 2007). By 1980, most new African arrivals were Black, shifting the African immigrant population from majority white in 1980 to majority Black by 1990 (Djamba 1999).…”
Section: African Immigrants and Economic Assimilation In The United Smentioning
confidence: 99%